Associations Among Diffusion Tensor Image Along the Perivascular Space (DTI-ALPS), Enlarged Perivascular Space (ePVS), and Cognitive Functions in Asymptomatic Patients With Carotid Plaque - Liu, Hui; Yang, Shuai; He, Wei; Liu, Xiaojuan; Sun, Shanyi; Wang, Song; Wang, Yang; Zhou, Xiaoliang; Tang, Tao; Xia, Jian; Liu, Yunhai; Huang, Qing (Frontiers in Neurology, 2022)
Background and Aim: Carotid atherosclerosis (CAS) is a common pathogenesis of cerebrovascular disease closely related to stroke and silent cerebrovascular disease (SCD), while the insufficient brain perfusion mechanism cannot quite explain the mechanism. The purpose of this study was to utilize diffusion tensor image analysis along the perivascular space (DTI-ALPS) to evaluate the glymphatic system activity and correlated DTI-ALPS with enlarged perivascular spaces (ePVS), carotid intima-media thickening (CIMT), mini-mental state examination (MMSE), and serological indicator in individuals with carotid plaque. Methods: Routine MRI and diffusion tensor images scan of the brain, carotid ultrasound, and blood examination were conducted on 74 individuals (52 carotid plaque subjects, 22 non-carotid plaque subjects), whose demographic and clinical characteristics were also recorded. DTI-ALPS index between patients with carotid plaque and normal controls were acquired and the correlations with other variables were analyzed. Results: The values of ALPS-index in the carotid plaque group was significantly lower compared to normal controls (2.12 ± 0.39, 1.95 ± 0.28, respectively, p = 0.034). The ALPS-index was negatively correlated with the basal ganglia (BG)-ePVS score (r = −0.242, p = 0.038) while there was no significant difference in the centrum semiovale (CSO)-ePVS score. Further analysis showed that there are more high-grade ePVS in the BG compared to the carotid plaque group than in the non-carotid plaque group (84.6% vs. 40.9%, p = 0.001). Conclusions: ALPS-index reflects the glymphatic system of the brain, which is associated with early high-risk cerebrovascular diseases. There may be damage in the function of the glymphatic system which induces the expansion of the perivascular space (PVS) in the BG in individuals with carotid plaque.